Concept of Ta’dib According to Syed M. Naquib al-Attas (An Analysis of Tasawuf Akhlaqi) - Sofian Hadi; Amir Reza Kusuma (LECTURES: Journal of Islamic and Education Studies, 2025)
The concept of ta'dib, initiated by Syed Muhammad Naquib al-Attas, represents a re-originalization of the foundations of education in Islam. The concept of ta'dib, in al-Attas's view, is deeper than the value and meaning of education itself. Through the concept of ta'dib, al-Attas explains three important things. First, recognition. Second, recognition. Third, wisdom (hikmah). The meaning of recognition is that humans acknowledge Allah as their creator. Recognition means that humans also acknowledge that when humans are sworn in by their God with the witness of the spirit. And wisdom (hikmah) here is a reflection of justice and etiquette. This paper uses an analytical method based on library research. The conclusion of the study shows that the concept of ta'dib as an Islamic educational concept leads to the formation of good men (good individuals) supported by intellectual intelligence and skills, which is one of the efforts that must be revived in the contemporary era.